1984
DOI: 10.1055/s-0038-1660998
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Small Pool High Yield Purified Factor VIII: In Vivo Recovery and Half-Life of Routinely Produced Freeze-Dried Concentrate

Abstract: SummaryNew approaches and techniques for improving source material collection and Factor VIII production at Blood Bank level have been reported recently.Heparin has been shown to be of importance in increasing yields and stability of FVIII in the purification and concentration process. Work has been done to develop on a routine scale the heparin double cold precipitation technique for the production of a freeze-dried high yield purified FVIII concentrate.The product has been tested clinically in 4 severe hemop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…We have previously reported that the FVIII level is considerably higher in heparinized plasma rather than citrated plasma with average values of 1.3 U/ml in heparin compared to 1.0 U/ml in citrate [2,3]. These results have been substantiated by others [4,5]. We [2] and Morgenthaler et al [4] have also found that heparin, added to citrate plasma or when used as a pri mary anticoagulant, significantly stabilizes FVIII so that a two-phase decay does not occur.…”
supporting
confidence: 56%
“…We have previously reported that the FVIII level is considerably higher in heparinized plasma rather than citrated plasma with average values of 1.3 U/ml in heparin compared to 1.0 U/ml in citrate [2,3]. These results have been substantiated by others [4,5]. We [2] and Morgenthaler et al [4] have also found that heparin, added to citrate plasma or when used as a pri mary anticoagulant, significantly stabilizes FVIII so that a two-phase decay does not occur.…”
supporting
confidence: 56%
“…Chelation of the calcium decreases the activity of FVIII that is not bound to vWF (Mikaelsson, Forsman & Oswaldsson, 1983;Rock et al, 1983;Farrugia et al, 1990). Also, in the presence of citrate, FVIII coagulant activity decreases during storage in a biphasic manner (Mikaelsson, Forsman & Oswaldsson, 1983) while collection of blood in heparin renders FVIII coagulant activity noticeably stable for at least 24 h (Krachmalnicoff & Thomas, 1983;Smit Sibinga et al, 1984;Morgenthaler, Zuber & Friedli, 1985;Cumming, Wensley & Delamore, 1986). Shanbrom and Owens (2001) have described the addition of a high concentration of sodium citrate to produce Ôsuper-cryoprecipitateÕ with a yield of both factor VIII and fibrinogen of 97%.…”
Section: Discussionmentioning
confidence: 99%
“…well as the good recovery, safety and normal half-disap pearance time of factor VIII derived from heparinized plasma [4,6,9]. Further, we have recently developed a factor VIII/von Willebrand factor concentrate that can be heat treated at 80°C for 72 h to inactivate potential viral contaminants [10].…”
Section: Introductionmentioning
confidence: 99%
“…Further, we have recently developed a factor VIII/von Willebrand factor concentrate that can be heat treated at 80°C for 72 h to inactivate potential viral contaminants [10]. The fractionation results obtained by our group were from heparinized plasma initially frozen and stored at -80°C for a period not in excess of 3 weeks [1,4] prior to routine cryoprecipitation at 4°C or were obtained by others [5,6,9] from plasma snap frozen at -70 °C in an alcohol-dry ice bath and then thawed at 4°C in a water bath for 75-90 min.…”
Section: Introductionmentioning
confidence: 99%